EFFECTIVE METHODS FROM NEW TECHNOLOGIES IN FOOTBALL - Nomozov , Abdurashid Tollibayevich (Innovative Development in Educational Activities, 2024)
In order to increase the effectiveness of training sessions, effective methods of introducing new technologies in football training are discussed.